2014
DOI: 10.3233/jpd-140368
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Genetic Susceptibility Model of Parkinson’s Disease Resulting from Exposure of DJ-1 Deficient Mice to MPTP: Evaluation of Neuroprotection by Ubisol-Q10

Abstract: Introduction: Parkinson's disease arises from a combination of environmental and genetic risk factors. At present neither the curative nor preventative therapies are available; hence, there is an urgent need to develop reliable animal models to facilitate their development. Water soluble nanomiceller formulation of CoQ 10 (Ubisol-Q 10) has shown neuroprotection against neurotoxin on human neuronal cells. We have combined the genetic deficiency of DJ-1/PARK7 mice with MPTP exposure and develop a genetic suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Chronic PQ or MPTP exposure in rats or mice is known to cause impaired motor performance on the rotarod task [14,35,36,46]. As already discussed, we focused our analysis on comparing the groups' proportion of head-down positions as they walked on a slowly rotating (6 rpm), 5-cm cylinder (rotarod) (Figure 2).…”
Section: Effect Of Ubisol-q 10 and Ashwagandha Extract On Pq-induced Motor Deficitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic PQ or MPTP exposure in rats or mice is known to cause impaired motor performance on the rotarod task [14,35,36,46]. As already discussed, we focused our analysis on comparing the groups' proportion of head-down positions as they walked on a slowly rotating (6 rpm), 5-cm cylinder (rotarod) (Figure 2).…”
Section: Effect Of Ubisol-q 10 and Ashwagandha Extract On Pq-induced Motor Deficitsmentioning
confidence: 99%
“…When combined with PTS, doses of coenzyme-Q 10 were able to be reduced significantly to 6 mg/kg/day. Ubisol-Q 10 has been shown to target mitochondrial dysfunction and oxidative stress in in vitro and in vivo models of PD [14,[32][33][34][35]. Furthermore, Ubisol-Q 10 prevented oxidative-stress-induced premature senescence and resumed impaired autophagy in Alzheimer's Disease (AD) fibroblasts, while also improving memory and removing beta-amyloid plaques in a transgenic mouse model of AD [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors appeared to improve and worsen the pathology of PD (Klingelhoefer and Reichmann, 2015; Delamarre and Meissner, 2017; Erro et al, 2018; Hu et al, 2019). Several chemicals or pesticides such as MPTP (Muthukumaran et al, 2014), paraquat (Park et al, 2005; Barlow et al, 2007), rotenone (Betarbet et al, 2000), viral infections (Bhattacharjee and Lukiw, 2013), etc., exposure to which lead to neurodegenerative effects whilst enriched environmental (EE) conditions based on studies of animal models suggested that enrichment can promote neuronal activation, signaling and plasticity in various brain regions. Therefore, EE conditions could possibly exert neuroprotective effects on neurons and delay pathogenesis in PD (Jadavji et al, 2006; Nithianantharajah and Hannan, 2006; Kotloski and Sutula, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of proper treatment available for GI dysmotility among PD patients, it is essential to discover new therapies that allow us to improve not only motor symptoms, but also non-motor symptoms, including cognitive impairment and dysfunction of the autonomic nervous system, and thereby modulate disease progression. PD may be initiated and/or precipitated by environmental or endogenous toxins by a mechanism similar to that of MPTP in genetically predisposed individuals [27]. The MPTP model has been widely accepted as a PD model that shows parkinsonogenic effects [28, 29].…”
Section: Introductionmentioning
confidence: 99%